The new information manager / Normurniza Md. Salleh, Nurul Basyira Basri and Sharmilla Rejab - Md. Salleh, Normurniza; Basri, Nurul Basyira; Rejab, Sharmilla (Faculty of Information Management, 2014)
According of Cambridge Business English Dictionary, the information manager is a person who is responsible for the systems that provide information to the people in an organization and he or she must know how to protecting the information.